IMPLEMENTASI PENDIDIKAN HOLISTIK DI PONDOK PESANTREN AMANATUL UMMAH MOJOKERTO - Ma`arif, Muhammad Anas; Rusydi, Ibnu (Badan Litbang dan Diklat Kementerian Agama RI, 2020)
AbstractThe purpose of this study was to describe and analize the implementation of holistic education in Amanatul Ummah Islamic Boarding School which is exploring in the terms of educational objectives, curriculum, learning methods, educators and evaluation. This study was uses qualitative approach research with the type of case study. That was describing and analyzing the implementation of holistic education in the Amanatul Islamic Boarding School. Implementation of holistic education in the Amanatul Ummah boarding school were carried out in a strict, responsible and disciplined manner while carrying out all things. The whole educational process from several elements includes: 1) Educational Objectives: the purpose of education in general is to form a whole human being with moral character while specifically covering. Becoming a cleric, a conglomerate, the nation's leader, and be a professional in every fields. 2) curriculum that implemented by using an integrative curriculum between the national curriculum and the standard of Al-Azhar Egyptâ€™s curriculum. 3) Educators are demanded to be professional and has excellent personalities for being a role of models for santri. 4), the methods that applied was various, including traditional methods and contemporary methods. 5). Evaluation: the evaluation was carried out every week, monthly, semester, and yearly. All educational elements are evaluated to realize the Islamic Boarding School's vision and mission.Â AbstrakPenelitian ini bertujuan untuk mendeskripsikan dan menganalisis implementasi pendidikan holistik pesantren Amanatul Ummah yang dieksplorasi dari segi tujuan pendidikan, kurikulum, metode pembelajaran, pendidik dan evaluasi. Penelitian ini menggunakan penelitian pendekatan kualitatif dengan jenis studi kasus, yaitu mendeskripsikan dan menganalisis implementasi pendidikan holistik di Pesantren Amanatul Ummah Mojokerto. Hasil penelitian Implementasi pendidikan holistik di pesantren Amanatul Ummah Mojokerto dilaksanakan dengan ketat, bertanggung jawab dan disiplin dalam melaksanakan segala hal. Penerapan proses pendidikan secara utuh dari beberapa elemen meliputi: 1). Tujuan pendidikan secara umum adalah membentuk manusia utuh yang berakhlakul karimah sedangkan secara khusus meliputi. Menjadi ulama`, menjadi konglomerat, menjadikan pemimpin bangsa, menjadi profesional di bidangnya. 2) kurikulum yang diimplementasikan menggunakan kurikulum integratif antara kurikulum nasional dengan kurikulum muadalah berstandar Al-Azhar Mesir. 3) Pendidik dituntut untuk profesional dan memiliki kepribadian yang mantap agar menjadi teladan bagi santri. 4), metode yang diterapkan bervariasi meliputi metode tradisional dan metode kontemporer. 5). Evaluasi: pelaksanaan evaluasi dilakukan setiap mingguan, bulanan, per semester, dan tahunan. Semua elemen pendidikan dievaluasi untuk mewujudkan visi-misi pesantren.